A Review Paper on Natural and Synthetic Refrigerants (International Journal of Innovative Research in Engineering & Management, 2023)
The Montreal Protocol (1987) prohibited  halogenated hydrocarbons with a high ozone depletion  potential (ODP) because of their harmful effects on the  ozone layer, which protects the earth from UV radiation.  The greenhouse gases (GHG) utilized in contemporary  refrigeration, air conditioning, and heat-pumping systems  are subject to a time-limited permit term under the Kyoto  Protocol (1997). The European Union law (2014) and the  Paris Accord (2016) place a significant emphasis on the  phase-out of hazardous synthetic refrigerants in order to  prevent ozone depletion and reverse climate change  impacts. The usage of natural refrigerants results in no net  increase in greenhouse gas (GHG) emissions in the  environment. Extensive research is being conducted  globally to adapt and alter current cooling and heating  systems utilizing natural refrigerants. This study uses the  Refrigerant Qualitative Parametric (RQP) quantification  model to examine timeworn, current, and next-generation  refrigerants in order to aid the refrigerant selection  process. It is calculated using the arithmetic sums of real  refrigerant parametric values adjusted to corresponding  ideal values. This model may aid in the selection of  alternative refrigerants for temporary replacement of  CFCs with HCFCs or HFCs, and eventual replacement of  HCFCs or HFCs with low GWP and ODP synthetic and  natural refrigerants.
Keywords: Global Warming; Natural; Refrigerants; Synthetic; Transport